2022
DOI: 10.1002/eng2.12502
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hybrid nanofluids (Ag‐TiO2/H2O) on improving the performance of a heat exchanger with turbulent induction elements

Abstract: In this article, the optimization of a twisted strip heat exchanger was explored aiming at enhancing heat transfer. To this end, governing equations using ANSYS‐FLUENT software and nanofluid flow using the k‐ε RNG turbulence model were simulated in the heat exchanger, respectively. The investigated parameters included temperature, pressure, velocity, turbulence kinetic energy (TKE), nanofluid concentration, nanofluid shape factor, Reynolds number, and the diameter of the spherical obstacle on the twisted tape.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Bisheh et al, [17] investigated the Impact of hybrid nanofluids (Ag-TiO2/Water) at 1.5-3-6% concentration with10000-18000 Re on improving the performance of a heat exchanger with turbulent induction elements and concluded that the heat transfer coefficient had increased by 52% at 6% of Ag-TiO2/ Water. Elfaghi et al, [18] studied the Forced Convection Heat Transfer Enhancement in Pipes numerically Using Al2O3/Water Nanofluid with (0.5-1-2% of concentration) in the Reynolds number range from 6000 to 12000.…”
Section: Introductionmentioning
confidence: 99%
“…Bisheh et al, [17] investigated the Impact of hybrid nanofluids (Ag-TiO2/Water) at 1.5-3-6% concentration with10000-18000 Re on improving the performance of a heat exchanger with turbulent induction elements and concluded that the heat transfer coefficient had increased by 52% at 6% of Ag-TiO2/ Water. Elfaghi et al, [18] studied the Forced Convection Heat Transfer Enhancement in Pipes numerically Using Al2O3/Water Nanofluid with (0.5-1-2% of concentration) in the Reynolds number range from 6000 to 12000.…”
Section: Introductionmentioning
confidence: 99%